Short-Term Celecoxib Promotes Bone Formation without Compromising Cefazolin Efficacy in an Early Orthopaedic Device-Related Infection: Evidence from a Rat Model - Vuyisa Siphelele Mdingi; Lena Gens; Karen Mys; Peter Varga; Stephan Zeiter; Leonard Charles Marais; Robert Geoffrey Richards; Fintan Thomas Moriarty; Marco Chittò (MDPI AG, 2024)
Non-steroidal anti-inflammatory drugs (NSAIDs) are crucial components of multimodal analgesia for musculoskeletal injuries, targeting cyclooxygenase (COX) enzymes (COX-1 and/or COX-2 isoenzymes). Concerns exist regarding their potential interference with bone healing and orthopaedic device-related infections (ODRI), where data are limited. This study aimed to investigate whether the COX-selectivity of NSAIDs interfered with antibiotic efficacy and bone changes in the setting of an ODRI. In vitro testing demonstrated that combining celecoxib (a COX-2 inhibitor) with cefazolin significantly enhanced antibacterial efficacy compared to cefazolin alone (p < 0.0001). In vivo experiments were performed using Staphylococcus epidermidis in the rat proximal tibia of an ODRI model. Long and short durations of celecoxib treatment in combination with antibiotics were compared to a control group receiving an antibiotic only. The long celecoxib treatment group showed impaired infection clearance, while the short celecoxib treatment showed increased bone formation (day 6, p < 0.0001), lower bone resorption (day 6, p < 0.0001), and lower osteolysis (day 6, BV/TV: p < 0.0001; BIC: p = 0.0005) compared to the control group, without impairing antibiotic efficacy (p > 0.9999). Given the use of NSAIDs as part of multimodal analgesia, and considering these findings, short-term use of COX-2 selective NSAIDs like celecoxib not only aids pain management but also promotes favorable bone changes during ODRI.